Positive plate and preparation method thereof, lithium ion battery and electric device

By doping nickel-cobalt lithium manganese phosphate positive electrode material to form a multi-layer structure positive electrode sheet, the problem of insufficient conductivity and compaction density is solved, the problem of manganese element dissolution is alleviated, and the lithium-ion battery is significantly improved electrochemical properties.

CN119208526APending Publication Date: 2024-12-27BATTEROTECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411375166.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have problems such as low electronic conductivity, low compaction density and manganese element dissolution in applications, resulting in poor electrochemical performance, which in turn affects the overall performance of lithium-ion batteries.

Method used

By doping nickel-cobalt lithium manganese phosphate into lithium manganese phosphate, a multi-layer structure positive electrode sheet is formed, using nickel-cobalt lithium manganese phosphate to improve conductivity and compaction density, and hindering the dissolution of manganese ions through the third coating, improving the overall structure Electrochemical properties.

Benefits of technology

It significantly improves the electrochemical performance of the positive electrode sheet and the electrochemical performance of lithium-ion batteries, including enhancing conductivity, compacting density and extending battery life, reducing the dissolution problem of manganese elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208526A_ABST
    Figure CN119208526A_ABST
Patent Text Reader

Abstract

The invention provides a positive plate and a preparation method thereof, a lithium ion battery and an electric device, and belongs to the technical field of lithium ion batteries. The positive plate comprises a first coating, a second coating, a third coating and a current collector. A first coating is arranged on the surface of one side of the current collector, a second coating and a third coating are sequentially arranged on the surface of the side, away from the current collector, of the first coating in a stacked mode, and the second coating is located between the first coating and the third coating. Each of the first coating and the third coating comprises a first active material, and the mass ratio of the first active material in the first coating or the third coating is 96-97.6%. The second coating comprises a second active material, and the mass ratio of the second active material in the second coating is 95-96.5%. The first active material is nickel cobalt lithium manganate, and the second active material is a mixture of nickel cobalt lithium manganate and lithium manganese iron phosphate. By arranging the first coating and the third coating and doping the lithium manganese iron phosphate with the nickel cobalt lithium manganate, the electrochemical performance of the positive plate can be improved, so that the electrochemical performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field, and specifically to a positive electrode sheet and a preparation method thereof, a lithium-ion battery and an electrical device. Background Art

[0002] Lithium iron manganese phosphate is a new type of positive electrode active material, which has attracted much attention due to its high theoretical energy density and good thermal stability. With the rapid development of electric vehicles and energy storage systems, the market demand for high-performance electrode active materials is growing, making lithium iron manganese phosphate a research hotspot.

[0003] When the existing lithium iron manganese phosphate material is used as a positive electrode active material, it mainly has the problems of low electronic conductivity, low compaction density and dissolution of manganese element, which makes the electrochemical performance of the lithium iron manganese phosphate material poor in practical applications, resulting in the positive electrode sheet using the lithium iron manganese phosphate material also having poor electrochemical performance, and further making the electrochemical performance of the lithium-ion battery using lithium iron manganese phosphate poor. Summary of the invention

[0004] The present application provides a positive electrode sheet and a preparation method thereof, a lithium ion battery and an electrical device, which can improve the electrochemical performance of the positive electrode sheet.

[0005] In the first aspect, the present application provides a positive electrode sheet, including a first coating, a second coating, a third coating and a current collector. A first coating is provided on one side surface of the current collector, and a second coating and a third coating are sequentially stacked on the side surface of the first coating away from the current collector, and the second coating is located between the first coating and the third coating. The first coating and the third coating both include a first active material, and the mass proportion of the first active material in the first coating or the third coating is 96 to 97.6%. The second coating includes a second active material, and the mass proportion of the second active material in the second coating is 95 to 96.5%. The first active material is lithium nickel cobalt manganese oxide, and the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium manganese iron phosphate.

[0006] Through the above scheme, compared with lithium manganese iron phosphate, lithium nickel cobalt manganese oxide has better conductivity and higher compaction density. Therefore, by mixing and doping lithium nickel cobalt manganese oxide in lithium manganese iron phosphate, the low conductivity and low compaction density of lithium manganese iron phosphate can be improved, so that the second coating has better conductivity and higher compaction density, so that the electrochemical performance of the positive electrode sheet is improved, thereby improving the electrochemical performance of the lithium ion battery. The third coating can not only improve the conductivity and compaction density through lithium nickel cobalt manganese oxide, but also can cover the second coating to prevent the direct contact between the second coating and the electrolyte and the dissolution of manganese ions during the charging and discharging process, so as to alleviate the problem of manganese element dissolution in lithium manganese iron phosphate, so that the electrochemical performance of the positive electrode sheet is improved, thereby improving the electrochemical performance of the lithium ion battery. The lithium nickel cobalt manganese oxide in the first coating can not only improve the conductivity between the current collector and the second coating, so that the conductivity of the positive electrode sheet is improved, but also can improve the overall compaction density of the positive electrode sheet through the characteristics of the high compaction density of lithium nickel cobalt manganese oxide, so as to improve the electrochemical performance. In summary, by providing the first coating and the third coating and doping lithium nickel cobalt manganese oxide into lithium manganese iron phosphate, the electrochemical properties of the positive electrode sheet can be improved, thereby improving the electrochemical properties of the lithium-ion battery.

[0007] In a possible design, the first coating and the third coating further include a first conductive agent, and the second coating further includes a second conductive agent. The mass proportion of the first conductive agent in the first coating or the third coating is 0.6-1.5%, and the mass proportion of the second conductive agent in the second coating is 1.5-2.5%. The first conductive agent includes conductive carbon black and carbon nanotubes, and the second conductive agent includes conductive graphite and carbon nanotubes.

[0008] Through the above scheme, since the conductive graphite has a regular layered crystal structure, and the conductive carbon black is composed of amorphous carbon, the conductivity of the conductive graphite itself is better than that of the conductive carbon black. Therefore, compared with conductive carbon black, the use of conductive graphite and carbon nanotubes can better improve the conductivity of the second coating layer. Since the conductivity of lithium iron manganese phosphate is low, the amount of the second conductive agent in the second coating layer is appropriately increased in actual production applications to improve the conductivity of the second coating layer to improve the electrochemical performance of the positive electrode sheet. Since the conductivity of lithium nickel cobalt manganese oxide is high, and the application cost of conductive graphite is higher than the application cost of conductive carbon black, the use of conductive carbon black and carbon nanotubes as the first conductive agent can reduce the production cost of the first coating layer and the third coating layer while not significantly affecting the conductivity of the first coating layer and the third coating layer, thereby reducing the production and processing cost of the positive electrode sheet.

[0009] In a possible design, the thickness of the second coating layer is greater than the thickness of the first coating layer or the third coating layer.

[0010] Through the above scheme, since the main functions of the first coating and the third coating are to improve the performance of lithium iron manganese phosphate, and the second coating mainly plays the role of energy storage, the second coating needs to be thicker to meet the electrochemical properties of the positive electrode sheet. The first coating and the third coating can be designed with a thinner thickness, which can reduce the production and processing cost of the positive electrode sheet while playing an improvement role, so as to facilitate the promotion and application of positive electrode sheets and even lithium-ion batteries.

[0011] In one possible design, the current collector is a carbon-coated aluminum foil.

[0012] Through the above scheme, compared with the common ordinary aluminum foil material, the carbon-coated aluminum foil is mainly made by setting a carbon coating layer on the surface of the aluminum foil material. Due to the good conductivity of the carbon coating layer, the carbon-coated aluminum foil can improve the conductivity of the positive electrode sheet and reduce the internal resistance of the lithium-ion battery. And because of its good flexibility, the carbon coating layer can increase the contact area with the positive electrode material, thereby reducing the contact resistance of the positive electrode sheet and improving the conductivity, so as to improve the electrochemical performance of the lithium-ion battery. In addition, due to the coating isolation of the carbon coating layer, the carbon-coated aluminum foil can reduce the loose bonding and powder loss caused by the change of the electrode volume during the cyclic charge and discharge process, thereby enhancing the structural stability of the battery and improving the cycle life of the battery.

[0013] In a second aspect, the present application provides a lithium-ion battery, comprising a negative electrode sheet, a separator and a positive electrode sheet, wherein the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and the separator is located between the positive electrode sheet and the negative electrode sheet.

[0014] The beneficial effects of the lithium-ion battery provided in the second aspect and each possible design of the second aspect can refer to the beneficial effects brought about by the first aspect and each possible implementation method of the first aspect, which will not be repeated here.

[0015] In a third aspect, the present application provides an electrical device including a lithium-ion battery.

[0016] The beneficial effects of the electrical device provided in the third aspect and each possible design of the third aspect can be referred to the beneficial effects brought about by the first aspect and each possible implementation method of the first aspect, and will not be repeated here.

[0017] In a fourth aspect, the present application provides a method for preparing a positive electrode sheet, comprising the steps of:

[0018] The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0019] The first slurry is evenly coated on the surface of the current collector and dried to obtain a first coating.

[0020] The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0021] The second slurry is evenly coated on the surface of the first coating layer, and after drying, the second coating layer is obtained.

[0022] The first slurry is evenly coated on the surface of the second coating layer, and after drying, the third coating layer is obtained.

[0023] Among them, in the first slurry, the mass ratio of the first active material, the first conductive agent, and the binder is (96-97.6): (0.6-1.5): (1.8-2.5). In the second slurry, the mass ratio of the second active material, the second conductive agent, and the binder is (95-96.5): (1.5-2.5): (2-2.5). The first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium manganese iron phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, and the current collector is carbon-coated aluminum foil.

[0024] In a possible design, the coating thickness of the first coating layer or the third coating layer is 5-10 μm, and the coating thickness of the second coating layer is 80-140 μm.

[0025] In a possible design, in the second active material, the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron phosphate is x:(1-x), 0 <x<1。

[0026] In a possible design, the binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polyimide, and / or the solvent includes N-methylpyrrolidone.

[0027] The beneficial effects of the method for preparing the positive electrode sheet provided in the second aspect and each possible design of the second aspect can be referred to the beneficial effects brought about by the first aspect and each possible implementation method of the first aspect, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of the overall structure of a positive electrode sheet provided in an embodiment of the present application.

[0029] Figure symbols: 1, positive electrode sheet; 11, current collector; 12, first coating; 13, second coating; 14, third coating. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification, claims and drawings of this application are intended to cover non-exclusive inclusions.

[0032] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0033] The term "and / or" in this article is only a description of the association relationship of the associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0034] The directional words appearing in the following description are all directions shown in the figures, and do not limit the specific structure of the current limiting module of the present application. For example, in the description of the present application, the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the drawings, which are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0035] In addition, the terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects rather than to describe a specific order, and may explicitly or implicitly include one or more of the features.

[0036] The present application discloses a bare cell, a battery cell and an electric device, wherein the battery cell includes the bare cell, the electric device includes the battery cell, and can be provided with electric energy by the battery cell. The electric device may be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, an electric tool, an energy storage device, an amusement device, an elevator and a lifting device, etc. The vehicle may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. The spacecraft may include an airplane, a rocket, a space shuttle and a spacecraft, etc. The electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy or an electric airplane toy, etc. The electric tool may include a metal cutting electric tool, a grinding electric tool, an assembly electric tool and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator and an electric planer, etc. The energy storage device may be an energy storage wall, a base station energy storage, a container energy storage, etc. The amusement device may be a carousel, a jumping machine, etc. This application does not impose any special restrictions on the above-mentioned electrical equipment.

[0037] For new energy vehicles, the above-mentioned battery cells can be used as driving power sources, thereby replacing fossil fuels to provide driving power.

[0038] Generally, a battery cell includes a battery casing and a bare cell, and the bare cell is contained in the battery casing. The bare cell is the smallest unit in the battery that performs electrochemical reactions and realizes the charging and discharging of the battery cell. It usually includes a positive electrode sheet, a negative electrode sheet, and a diaphragm that separates the positive electrode sheet from the negative electrode sheet. The battery casing is injected with an electrolyte, which can infiltrate the inside of the bare cell, providing an ion migration path for the bare cell to perform electrochemical reactions and playing a conductive role.

[0039] The problem of manganese dissolution in lithium manganese iron phosphate materials is mainly related to the following factors:

[0040] 1. Redox reaction of manganese ions:

[0041] During the charging and discharging process of lithium manganese iron phosphate batteries, manganese ions undergo redox reactions. When the battery is in the discharge state, manganese ions are oxidized from a trivalent state (or higher) to a tetravalent state, while releasing electrons; in the charging state, manganese ions are reduced to a trivalent state (or lower) while absorbing electrons.

[0042] During this redox reaction, the change in the valence state of manganese ions will cause changes in their stability, which in turn causes the problem of manganese dissolution.

[0043] 2. Crystal structure and chemical properties of positive electrode materials:

[0044] The lithium manganese oxide in lithium manganese iron phosphate batteries usually adopts a cubic crystal structure, but phase changes will occur during the charge and discharge process to form other crystal structures. These changes in crystal structure will affect the stability and solubility of manganese ions.

[0045] The chemical properties of the cathode material are also an important factor affecting manganese dissolution. For example, when the fluoride ion content in the cathode material is high, the solubility of manganese ions can be reduced.

[0046] 3. Influence of electrolyte:

[0047] The composition and properties of the electrolyte have a significant impact on the manganese dissolution problem. Certain ions or molecules in the electrolyte may react with manganese ions and promote the dissolution of manganese.

[0048] Optimizing the formulation and properties of the electrolyte is one of the important ways to solve the problem of manganese dissolution. For example, by adjusting the composition and concentration of the electrolyte, the side reaction of manganese with the electrolyte can be reduced, thereby reducing the solubility of manganese.

[0049] 4. The Jiang Taylor Effect:

[0050] When the manganese content in lithium manganese iron phosphate is too high, the Jan-Taylor effect will occur. This effect causes manganese ions to dissolve and deposit on the negative electrode surface during charging and discharging, destroying the SEI film (solid electrolyte interface film), thereby consuming a large amount of active lithium and causing capacity loss.

[0051] like Figure 1 As shown, the present application provides a positive electrode sheet 1, comprising a first coating 12, a second coating 13, a third coating 14 and a current collector 11. The first coating 12 is provided on one side surface of the current collector 11, and the second coating 13 and the third coating 14 are sequentially stacked on the side surface of the first coating 12 away from the current collector 11, and the second coating 13 is located between the first coating 12 and the third coating 14. The first coating 12 and the third coating 14 both include a first active material, and the mass proportion of the first active material in the first coating 12 or the third coating 14 is 96-97.6%. The second coating 13 includes a second active material, and the mass proportion of the second active material in the second coating 13 is 95-96.5%. The first active material is lithium nickel cobalt manganese oxide, and the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium manganese iron phosphate.

[0052] Compared with lithium manganese iron phosphate, lithium nickel cobalt manganese oxide has better conductivity and higher compaction density.

[0053] Therefore, by mixing and doping lithium nickel cobalt manganese oxide into lithium manganese iron phosphate, the problems of low conductivity and low compaction density of lithium manganese iron phosphate can be improved, so that the second coating 13 has better conductivity and higher compaction density, so that the electrochemical properties of the positive electrode sheet 1 are improved, thereby improving the electrochemical properties of the lithium-ion battery.

[0054] The third coating 14 can not only improve the conductivity and compaction density through lithium nickel cobalt manganese oxide, but also can cover the second coating 13 to hinder the direct contact between the second coating 13 and the electrolyte and the dissolution of manganese ions during the charging and discharging process, so as to alleviate the problem of manganese element dissolution in lithium manganese iron phosphate, improve the electrochemical performance of the positive electrode sheet 1, and thus improve the electrochemical performance of the lithium-ion battery.

[0055] The lithium nickel cobalt manganese oxide in the first coating 12 can not only improve the conductivity between the current collector 11 and the second coating 13, thereby improving the conductivity of the positive electrode sheet 1, but also can improve the overall compaction density of the positive electrode sheet 1 through the high compaction density of the lithium nickel cobalt manganese oxide, thereby improving the electrochemical performance.

[0056] In summary, by providing the first coating 12 and the third coating 14 and doping lithium nickel cobalt manganese oxide into lithium manganese iron phosphate, the electrochemical performance of the positive electrode sheet 1 can be improved, thereby improving the electrochemical performance of the lithium-ion battery.

[0057] The mass percentage of the first active material in the first coating layer 12 or the third coating layer 14 can be 96%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 96.6%, 96.7%, 96.8%, 96.9%, 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, etc.

[0058] In actual production applications, the mass proportion of the first active material in the first coating layer 12 may be the same as or different from the mass proportion of the first active material in the third coating layer 14. The specific amount of the first active material may be adjusted according to actual needs.

[0059] The mass proportion of the second active material in the second coating 13 can be 95%, 95.1%, 95.2%, 95.3%, 95.4%, 95.5%, 95.6%, 95.7%, 95.8%, 95.9%, 96%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, etc.

[0060] Optionally, the first coating 12 and the third coating 14 further include a first conductive agent, and the second coating 13 further includes a second conductive agent. The mass proportion of the first conductive agent in the first coating 12 or the third coating 14 is 0.6-1.5%, and the mass proportion of the second conductive agent in the second coating 13 is 1.5-2.5%. The first conductive agent includes conductive carbon black and carbon nanotubes, and the second conductive agent includes conductive graphite and carbon nanotubes.

[0061] Since conductive graphite has a regular layered crystal structure, and conductive carbon black is composed of amorphous carbon, the conductivity of conductive graphite itself is better than that of conductive carbon black. Therefore, compared with conductive carbon black, the use of conductive graphite and carbon nanotubes in combination can better improve the conductivity of the second coating 13.

[0062] Since lithium manganese iron phosphate has a low conductivity, appropriately increasing the amount of the second conductive agent in the second coating layer 13 in actual production applications can improve the conductivity of the second coating layer 13 to enhance the electrochemical performance of the positive electrode sheet 1 .

[0063] Since lithium nickel cobalt manganese oxide has a high conductivity and the application cost of conductive graphite is higher than that of conductive carbon black, conductive carbon black and carbon nanotubes are used in combination as the first conductive agent. This will not significantly affect the conductivity of the first coating 12 and the third coating 14, while also reducing the production costs of the first coating 12 and the third coating 14, thereby reducing the production and processing costs of the positive electrode sheet 1.

[0064] Specifically, the mass proportion of the conductive carbon black in the first coating layer 12 or the third coating layer 14 may be 0.5-1%, and the mass proportion of the carbon nanotubes in the first coating layer 12 or the third coating layer 14 may be 0.1-0.5%.

[0065] The mass proportion of the conductive carbon black in the first coating layer 12 or the third coating layer 14 may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.

[0066] The mass proportion of the carbon nanotubes in the first coating layer 12 or the third coating layer 14 may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.

[0067] Specifically, the mass proportion of the conductive graphite in the second coating layer 13 may be 1-1.5%, and the mass proportion of the carbon nanotubes in the second coating layer 13 may be 0.5-1%.

[0068] The mass proportion of the conductive graphite in the second coating layer 13 may be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.

[0069] The mass proportion of the carbon nanotubes in the second coating layer 13 may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.

[0070] Optionally, the thickness of the second coating layer 13 is greater than the thickness of the first coating layer 12 or the third coating layer 14 .

[0071] Since the main functions of the first coating 12 and the third coating 14 are to improve the performance of lithium iron manganese phosphate, and the second coating 13 mainly plays the role of energy storage, the second coating 13 needs to be thicker to meet the electrochemical properties of the positive electrode sheet 1. The first coating 12 and the third coating 14 can be designed with a thinner thickness to reduce the production and processing cost of the positive electrode sheet 1 while playing an improvement role, so as to facilitate the promotion and application of the positive electrode sheet 1 and even lithium-ion batteries.

[0072] Optionally, the current collector 11 is a carbon-coated aluminum foil.

[0073] Compared with common ordinary aluminum foil materials, carbon-coated aluminum foil is mainly made by setting a carbon coating layer on the surface of the aluminum foil material. Since the carbon coating layer has good conductivity, the carbon-coated aluminum foil can improve the conductivity of the positive electrode sheet 1 and reduce the internal resistance of the lithium-ion battery. And because of its good flexibility, the carbon coating layer can increase the contact area with the positive electrode material, thereby reducing the contact resistance of the positive electrode sheet 1 and improving the conductivity, so as to improve the electrochemical performance of the lithium-ion battery.

[0074] In addition, due to the coating and isolation of the carbon coating layer, the carbon-coated aluminum foil can reduce the loosening and powder loss caused by the volume change of the electrode during the cyclic charge and discharge process, thereby enhancing the structural stability of the battery and improving the cycle life of the battery. The carbon coating layer can also delay the corrosion of the aluminum foil by the oxidation decomposition products of the electrolyte, protect the aluminum foil, and improve the reliability and life of the battery.

[0075] The present application provides a method for preparing a positive electrode sheet, comprising the steps of:

[0076] The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0077] The first slurry is evenly coated on the surface of the current collector and dried to obtain a first coating.

[0078] The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0079] The second slurry is evenly coated on the surface of the first coating layer, and after drying, the second coating layer is obtained.

[0080] The first slurry is evenly coated on the surface of the second coating layer, and after drying, the third coating layer is obtained.

[0081] Among them, in the first slurry, the mass ratio of the first active material, the first conductive agent, and the binder is (96-97.6): (0.6-1.5): (1.8-2.5). In the second slurry, the mass ratio of the second active material, the second conductive agent, and the binder is (95-96.5): (1.5-2.5): (2-2.5). The first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium manganese iron phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, and the current collector is carbon-coated aluminum foil.

[0082] Optionally, the coating thickness of the first coating layer or the third coating layer is 5 to 10 μm, and the coating thickness of the second coating layer is 80 to 140 μm.

[0083] Specifically, the coating thickness of the first coating layer or the third coating layer may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0084] The coating thickness of the second coating layer may be 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, etc.

[0085] Optionally, in the second active material, the mass ratio of lithium nickel cobalt manganese oxide to lithium manganese iron phosphate is x:(1-x), 0 <x<1。

[0086] Optionally, the binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polyimide. And / or, the solvent includes N-methylpyrrolidone.

[0087] Specifically, polyvinylidene fluoride is selected as a binder in this application. Polyvinylidene fluoride has excellent bonding properties, good chemical resistance, excellent heat resistance, and good weather resistance, so that each part of the positive electrode sheet can maintain good bonding in the working environment to ensure that the positive electrode sheet can work normally, so that the lithium-ion battery maintains good working stability and reliability. In addition, because polyvinylidene fluoride has a low viscosity and is easy to apply when used as a binder, the difficulty of producing and processing the positive electrode sheet is reduced, which is conducive to improving the production and processing efficiency of the positive electrode sheet and even the lithium-ion battery.

[0088] The present invention is described in detail below through specific examples. The examples are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0089] Example 1

[0090] 1. Preparation of positive electrode

[0091] 1.1 The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0092] 1.2 The first slurry is evenly coated on the surface of the current collector, and after drying, the first coating is obtained. The coating thickness is 5 μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0093] 1.3 The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0094] 1.4 The second slurry is evenly coated on the surface of the first coating, and after drying, the second coating is obtained. The coating thickness is 120 μm. After coating, the electrode piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0095] 1.5 The first slurry is evenly coated on the surface of the second coating layer, and after drying, a third coating layer is obtained to obtain a positive electrode sheet. The coating thickness is 5 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0096] Among them, the first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, the current collector is carbon-coated aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0097] In the first slurry, the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 96:1:0.5:2.5. In the second slurry, the mass ratio of the second active agent, conductive graphite, carbon nanotubes, and polyvinylidene fluoride is 95:1.5:1:2.5, and in the second active agent, the mass ratio of lithium nickel cobalt manganese oxide to lithium iron manganese phosphate is 2:8.

[0098] 2. Preparation of negative electrode

[0099] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0100] 3. Preparation of Lithium-ion Batteries

[0101] The positive electrode sheet prepared in the above step 1.5 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0102] Example 2

[0103] 1. Preparation of positive electrode

[0104] 1.1 The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0105] 1.2 The first slurry is evenly coated on the surface of the current collector, and after drying, the first coating is obtained. The coating thickness is 10 μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0106] 1.3 The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0107] 1.4 The second slurry is evenly coated on the surface of the first coating, and after drying, the second coating is obtained. The coating thickness is 130 μm. After coating, the electrode piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0108] 1.5 The first slurry is evenly coated on the surface of the second coating layer, and after drying, the third coating layer is obtained to obtain the positive electrode sheet. The coating thickness is 10 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0109] Among them, the first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, the current collector is carbon-coated aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0110] In the first slurry, the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 97.6:0.5:0.1:1.8. In the second slurry, the mass ratio of the second active agent, conductive graphite, carbon nanotubes, and polyvinylidene fluoride is 96.5:1:0.5:2, and in the second active agent, the mass ratio of lithium nickel cobalt manganese oxide to lithium iron manganese phosphate is 3:7.

[0111] 2. Preparation of negative electrode

[0112] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0113] 3. Preparation of Lithium-ion Batteries

[0114] The positive electrode sheet prepared in the above step 1.5 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0115] Example 3

[0116] 1. Preparation of positive electrode

[0117] 1.1 The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0118] 1.2 The first slurry is evenly coated on the surface of the current collector, and after drying, the first coating is obtained. The coating thickness is 8 μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0119] 1.3 The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0120] 1.4 The second slurry is evenly coated on the surface of the first coating, and after drying, the second coating is obtained. The coating thickness is 140 μm. After coating, the electrode piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0121] 1.5 The first slurry is evenly coated on the surface of the second coating layer, and after drying, a third coating layer is obtained to obtain a positive electrode sheet. The coating thickness is 8 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0122] Among them, the first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, the current collector is carbon-coated aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0123] In the first slurry, the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 97:0.7:0.3:2. In the second slurry, the mass ratio of the second active agent, conductive graphite, carbon nanotubes, and polyvinylidene fluoride is 95.7:1.2:0.8:2.3, and in the second active agent, the mass ratio of lithium nickel cobalt manganese oxide to lithium iron manganese phosphate is 4:6.

[0124] 2. Preparation of negative electrode

[0125] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0126] 3. Preparation of Lithium-ion Batteries

[0127] The positive electrode sheet prepared in the above step 1.5 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0128] Example 4

[0129] 1. Preparation of positive electrode

[0130] 1.1 The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0131] 1.2 The first slurry is evenly coated on the surface of the current collector, and after drying, the first coating is obtained. The coating thickness is 5 μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0132] 1.3 The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0133] 1.4 The second slurry is evenly coated on the surface of the first coating, and after drying, the second coating is obtained. The coating thickness is 80 μm. After coating, the electrode piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0134] 1.5 The first slurry is evenly coated on the surface of the second coating layer, and after drying, a third coating layer is obtained to obtain a positive electrode sheet. The coating thickness is 5 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0135] Among them, the first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, the current collector is carbon-coated aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0136] In the first slurry, the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 96:1:0.5:2.5. In the second slurry, the mass ratio of the second active agent, conductive graphite, carbon nanotubes, and polyvinylidene fluoride is 95:1.5:1:2.5, and in the second active agent, the mass ratio of lithium nickel cobalt manganese oxide to lithium iron manganese phosphate is 2:8.

[0137] 2. Preparation of negative electrode

[0138] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0139] 3. Preparation of Lithium-ion Batteries

[0140] The positive electrode sheet prepared in the above step 1.5 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0141] Example 5

[0142] 1. Preparation of positive electrode

[0143] 1.1 The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0144] 1.2 The first slurry is evenly coated on the surface of the current collector, and after drying, the first coating is obtained. The coating thickness is 10 μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0145] 1.3 The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0146] 1.4 The second slurry is evenly coated on the surface of the first coating, and after drying, the second coating is obtained. The coating thickness is 80 μm. After coating, the electrode piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0147] 1.5 The first slurry is evenly coated on the surface of the second coating layer, and after drying, the third coating layer is obtained to obtain the positive electrode sheet. The coating thickness is 10 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0148] Among them, the first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, the current collector is carbon-coated aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0149] In the first slurry, the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 97.6:0.5:0.1:1.8. In the second slurry, the mass ratio of the second active agent, conductive graphite, carbon nanotubes, and polyvinylidene fluoride is 96.5:1:0.5:2, and in the second active agent, the mass ratio of lithium nickel cobalt manganese oxide to lithium iron manganese phosphate is 3:7.

[0150] 2. Preparation of negative electrode

[0151] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0152] 3. Preparation of Lithium-ion Batteries

[0153] The positive electrode sheet prepared in the above step 1.5 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0154] Example 3

[0155] 1. Preparation of positive electrode

[0156] 1.1 The first active material, the first conductive agent and the binder are uniformly dispersed in a solvent to prepare a first slurry.

[0157] 1.2 The first slurry is evenly coated on the surface of the current collector, and after drying, the first coating is obtained. The coating thickness is 8 μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0158] 1.3 The second active material, the second conductive agent and the binder are uniformly dispersed in a solvent to prepare a second slurry.

[0159] 1.4 The second slurry is evenly coated on the surface of the first coating, and after drying, the second coating is obtained. The coating thickness is 80 μm. After coating, the electrode piece passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0160] 1.5 The first slurry is evenly coated on the surface of the second coating layer, and after drying, a third coating layer is obtained to obtain a positive electrode sheet. The coating thickness is 8 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s, and the baking temperature of the oven is 110 degrees.

[0161] Among them, the first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, the current collector is carbon-coated aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0162] In the first slurry, the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 97:0.7:0.3:2. In the second slurry, the mass ratio of the second active agent, conductive graphite, carbon nanotubes, and polyvinylidene fluoride is 95.7:1.2:0.8:2.3, and in the second active agent, the mass ratio of lithium nickel cobalt manganese oxide to lithium iron manganese phosphate is 4:6.

[0163] 2. Preparation of negative electrode

[0164] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0165] 3. Preparation of Lithium-ion Batteries

[0166] The positive electrode sheet prepared in the above step 1.5 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0167] Comparative Example

[0168] 1. Preparation of positive electrode

[0169] 1.1 Evenly disperse lithium manganese iron phosphate, conductive agent and binder in a solvent to prepare positive electrode slurry.

[0170] 1.2 The positive electrode slurry is evenly coated on the surface of the current collector and dried to obtain a positive electrode sheet.

[0171] The coating thickness is 140μm. After coating, the pole piece passes through a 20-meter-long oven at a speed of 3m / s, and the baking temperature of the oven is 110 degrees. The conductive agent includes conductive carbon black and carbon nanotubes, the current collector is aluminum foil, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone. The mass ratio of lithium iron manganese phosphate, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride is 97.6:0.5:0.1:1.8.

[0172] 2. Preparation of negative electrode

[0173] 2.1 The negative electrode slurry is evenly coated on the negative electrode current collector, and after drying, the negative electrode sheet is obtained. The coating thickness is 6 μm. After coating, the electrode sheet passes through a 20-meter-long oven at a speed of 3 m / s. The baking temperature of the oven is 110 degrees. The negative electrode current collector is selected as copper foil.

[0174] 3. Preparation of Lithium-ion Batteries

[0175] The positive electrode sheet prepared in the above step 1.2 and the negative electrode sheet prepared in the above step 2.1 are made into a soft-pack battery.

[0176] The performance of the positive electrode is tested using the following method:

[0177] (1) Compaction density test: The positive electrode sheet is rolled on a roller press with different compaction gradients. The rolled positive electrode sheet is folded in half to observe whether the positive electrode sheet is light-transmitting. The compaction density value of the positive electrode sheet when light is transmissive is recorded as the limiting compaction density.

[0178] (2) Penetration resistance test: Use the tester to connect the sample to be tested in series with an equivalent analog circuit, and measure the resistance by applying a certain voltage.

[0179] The electrochemical performance of lithium-ion batteries was tested using the following methods:

[0180] (1) Cycle test: The lithium-ion battery was placed in an environment of 45±2℃, and charged to 4.3V at a constant current of 0.5C, and then charged at a constant voltage until the current dropped to 0.05C, and then the charging was stopped, and then the battery was discharged to 2.7V at a constant current of 0.5C. The cycle was repeated for 500 cycles to test the battery capacity retention rate.

[0181] (2) Mn dissolution test: The lithium-ion battery that has completed the cycle test is disassembled and the Mn content of the negative electrode sheet is tested using an ICP tester.

[0182] The performance test results of the positive electrode sheets prepared in Examples 1 to 6 and Comparative Example 1 and the electrochemical performance test results of the lithium ion battery are summarized in Table 1.

[0183] Table 1

[0184] Through resistance / mΩ Compacted density / (g / cc) Capacity retention rate / % Mn content / ppm Example 1 276.0 2.54 93.6 746 Example 2 253.7 2.62 94.5 703 Example 3 229.2 2.75 95.9 689 Example 4 225.8 2.66 95.6 732 Example 5 216.4 2.79 96.1 672 Example 6 192.9 2.93 97.4 651 Comparative Example 331.3 2.42 93.1 830

[0185] The test results of the lithium-ion battery show that, compared with the lithium-ion battery in the comparative example, the capacity retention rate of the lithium-ion batteries in Examples 1 to 6 is significantly improved, and the Mn content measured on the negative electrode sheets is significantly reduced. Therefore, it is shown that the solution of the present application can improve the electrochemical performance of lithium-ion batteries.

[0186] The test results of the positive electrode sheets show that, compared with the positive electrode sheets in the comparative examples, the lithium-ion batteries in Examples 1 to 6 have significantly lower penetration resistance and significantly higher compaction density, which indicates that the solution of the present application can improve the performance of the positive electrode sheets.

[0187] In summary, the test results show that the solution of the present invention can effectively improve the performance of the positive electrode sheet and the electrochemical performance of the lithium-ion battery, thereby effectively improving the electrochemical performance of the lithium-ion battery using lithium iron manganese phosphate.

[0188] The above description is only a preferred embodiment of the present invention, and the above specific embodiment is not intended to limit the present invention. Various deformations and modifications may occur within the scope of the technical concept of the present invention, and any modification, modification or equivalent replacement made by a person of ordinary skill in the art based on the above description shall fall within the scope of protection of the present invention.

Claims

1. A positive electrode sheet, characterized in that: comprising a first coating layer, a second coating layer, a third coating layer and a current collector; The first coating is disposed on one side surface of the current collector, and the second coating and the third coating are sequentially stacked on the side surface of the first coating facing away from the current collector, and the second coating is located between the first coating and the third coating; The first coating layer and the third coating layer both include a first active material, and the mass proportion of the first active material in the first coating layer or the third coating layer is 96-97.6%; The second coating layer includes a second active material, and the mass proportion of the second active material in the second coating layer is 95-96.5%; The first active material is lithium nickel cobalt manganese oxide, and the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate.

2. The positive electrode sheet according to claim 1, characterized in that: The first coating layer and the third coating layer further include a first conductive agent, and the second coating layer further includes a second conductive agent; The mass proportion of the first conductive agent in the first coating or the third coating is 0.6-1.5%, and the mass proportion of the second conductive agent in the second coating is 1.5-2.5%; The first conductive agent includes conductive carbon black and carbon nanotubes, and the second conductive agent includes conductive graphite and carbon nanotubes.

3. The positive electrode sheet according to claim 1, characterized in that: The thickness of the second coating layer is greater than the thickness of the first coating layer or the third coating layer.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The current collector is carbon-coated aluminum foil.

5. A lithium ion battery, characterized in that: It comprises a negative electrode sheet, a separator and a positive electrode sheet as claimed in any one of claims 1 to 4, wherein the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and the separator is located between the positive electrode sheet and the negative electrode sheet.

6. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 5.

7. A method for preparing a positive electrode sheet according to any one of claims 1 to 4, characterized in that: Includes steps: Uniformly dispersing a first active material, a first conductive agent, and a binder in a solvent to prepare a first slurry; Uniformly coating the first slurry on the surface of the current collector and drying it to obtain a first coating; uniformly dispersing a second active material, a second conductive agent, and a binder in a solvent to prepare a second slurry; The second slurry is evenly coated on the surface of the first coating layer, and after drying, a second coating layer is obtained; The first slurry is evenly coated on the surface of the second coating layer, and after drying, a third coating layer is obtained; Wherein, in the first slurry, the mass ratio of the first active material, the first conductive agent, and the binder is (96-97.6):(0.6-1.5):(1.8-2.5); in the second slurry, the mass ratio of the second active material, the second conductive agent, and the binder is (95-96.5):(1.5-2.5):(2-2.5); The first active material is lithium nickel cobalt manganese oxide, the second active material is a mixture of lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the first conductive agent includes conductive carbon black and carbon nanotubes, the second conductive agent includes conductive graphite and carbon nanotubes, and the current collector is carbon-coated aluminum foil.

8. The preparation method according to claim 7, characterized in that: The coating thickness of the first coating layer or the third coating layer is 5 to 10 μm, and the coating thickness of the second coating layer is 80 to 140 μm.

9. The preparation method according to claim 7, characterized in that: In the second active material, the mass ratio of the lithium nickel cobalt manganese oxide to the lithium manganese iron phosphate is x:(1-x), 0 <x<1。 10. The preparation method according to any one of claims 7 to 9, characterized in that: The binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polyimide; And / or, the solvent comprises N-methylpyrrolidone.

Citation Information

Cited By

  • Positive pole piece, lithium ion battery comprising positive pole piece, and electronic device comprising positive pole piece

    CN122067976A